2022
DOI: 10.3389/fmolb.2022.1035574
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial cell membranes and their role in daptomycin resistance: A review

Abstract: Lipids play a major role in bacterial cells. Foremost, lipids are the primary constituents of the cell membrane bilayer, providing structure and separating the cell from the surrounding environment. This makes the lipid bilayer a prime target for antimicrobial peptides and membrane-acting antibiotics such as daptomycin. In response, bacteria have evolved mechanisms by which the membrane can be adapted to resist attack by these antimicrobial compounds. In this review, we focus on the membrane phospholipid chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…The daptomycin mechanism consists of membrane permeabilization, the inhibition of cell wall synthesis, and the alternation of membrane fluidity and curvature. Unfortunately, its extensive clinical use has already led to resistance due to alterations in the membrane lipid composition such as a significant decrease in the amount of phosphatidylglycerol (PG) or an increase in cardiolipin (CL), which limits daptomycin’s action against bacteria [ 99 ].…”
Section: Amp Lipidationmentioning
confidence: 99%
“…The daptomycin mechanism consists of membrane permeabilization, the inhibition of cell wall synthesis, and the alternation of membrane fluidity and curvature. Unfortunately, its extensive clinical use has already led to resistance due to alterations in the membrane lipid composition such as a significant decrease in the amount of phosphatidylglycerol (PG) or an increase in cardiolipin (CL), which limits daptomycin’s action against bacteria [ 99 ].…”
Section: Amp Lipidationmentioning
confidence: 99%
“…We observed that daptomycin bound evenly to the outside (mother) vesicle, however the vesicles in the lumen did not show fluorescence in the daptomycin channel, and presumably remained completely unaffected by its activity. According to recent molecular dynamics simulations, upon contact with Ca 2+ ions daptomycin forms tetramers, which can reversibly flip between the outer and inner leaflets of the membrane [102]. We cannot unambiguously conclude whether daptomycin embeds only in the outer leaflet or integrates also in the inner monolayer of the membrane.…”
Section: Resultsmentioning
confidence: 89%
“…Acute bacterial infection is the most common type of infection in clinical practice. Peritonitis, liver abscess, and other diseases caused by P. aeruginosa are also very common in hospitals (Nguyen et al 2022). In the present study, we designed an acute mouse abdominal infection model caused by P. aeruginosa to evaluate the in vivo e cacy of berberine hydrochloride.…”
Section: Disscussionmentioning
confidence: 99%